Longhorn Airlines : flying through turbulent times - Cox, Marcus, active 2021, (SAGE business cases, 2021)
Thomas Cox, CEO of regional carrier Longhorn Airlines, is concerned about the operational performance and customer satisfaction of the airline. The competitive nature of the airline industry sent numerous carriers out of business over the years. In an effort to remain viable, Thomas asks his VP of Operations, Anna Gates, to investigate technological enhancements that can improve operational efficiencies at Longhorn Airlines. The implementation of these new technologies will mean a restructuring of processes and as a result, a restructuring of employee compensation, as well as potential obsolescence of some positions within the organization, which students must factor into their decisions.